A Pilot Study of a Mindfulness-Based Art Therapy Intervention in Outpatients With Cancer. (September 2018) - Meghani, Salimah H.; Peterson, Caroline; Kaiser, Donna H.; Rhodes, Joseph; Rao, Hengyi; Chittams, Jesse; Chatterjee, Anjan
Background: Patients with cancer frequently experience physical and psychological distress that can worsen their quality of life. Objectives: We assessed the outcomes of an 8-week mindfulness-based art therapy (MBAT) intervention, Walkabout: Looking In, Looking Out, on symptoms, sleep quality, health-related quality of life, sense of coherence (SOC), and spirituality in outpatients with cancer. Methods: A 1-group, pre–post intervention design with repeated measures at baseline, week 4, and week 8. Results: Despite a small pilot sample (n = 18), we found large effect sizes and statistically significant improvements from week 1 to week 8 in depression, the comprehensibility subscale of the SOC, and each subscale of spirituality, that is, peace, meaning, and faith. There were no significant changes in physical functioning, pain, sleep, tiredness, drowsiness, nausea, and appetite. Conclusions: The MBAT intervention, Walkabout, seems to meet key palliative care goals including improvement in emotional well-being, comprehensibility, and meaning making among outpatients with cancer.